Key Political Topic in News Discourse: Analysis of Language Transformation in A Corpus-Based Critical Linguistic Perspective - ANTOK RISALDI (Buana Bastra, 2022)
This study aims to describe and explain key political topics in news discourse. The focus of this study is lexical and grammatical transformations in news discourse. In this study, a qualitative approach was used within the framework of a critical linguistic approach. In this study, we used korpora on the Corpora Leipzig online page. It aims to find out what words are related and often appear in the results of the concordance of political keywords. The data used is in the form of words, phrases, and sentences as representations of news titles from various Indonesian media sources in 2022. The analysis used in this study is only a two-level analysis, namely micro analysis and macro analysis. The findings of this study show that in lexical transformation using the words orthodoxy, failed coups, religious politicians, rinks, identities, money, officials, political parties, hoaxes, elections, dynasties, powers, elites, nationalities, and bureaucracies. For grammatical transformations use clauses or sentences that deal with how to organize subjects and predicates, including also objects, and complements.